2015
DOI: 10.1002/adsc.201500206
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Enantioselectivity in the Bioreduction of (Z)‐β‐Aryl‐β‐cyanoacrylates Mediated by the Tryptophan 116 Mutants of Old Yellow Enzyme 1: Synthetic Approach to (R)‐ and (S)‐β‐Aryl‐γ‐lactams

Abstract: TheT rp 116 mutantso fO ld Yellow Enzyme 1t hat catalyse the reductiono f( Z )-b-arylb-cyanoacrylates give the opposite enantioselectivity according to the nature of the amino acid in position 116. Small amino acids (e.g.,a lanine)m aket he substrate bind to the enzyme'sa ctive site in a" classical" orientation, affording the (S)-enantiomer of the reduced product.W hen the size of the amino acid increases( e.g.,l eucine), a" flipped" binding mode is adopted by the substrate,w hich is converted into the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…No activity towards 1 was observed with PETNR W102I, but other variants at this hotspot position and other substrates showed increased conversion . Incorporation of W116I into circular permutated OYE1 variants lowered conversion of 3 , a saturation mutagenesis library at W116 showed no hits for 1 , and biocatalytic characterisation of all 20 variants showed that W116I is not the best engineered residue for this position . Nevertheless, our NCR data support the importance of hotspot position III itself.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…No activity towards 1 was observed with PETNR W102I, but other variants at this hotspot position and other substrates showed increased conversion . Incorporation of W116I into circular permutated OYE1 variants lowered conversion of 3 , a saturation mutagenesis library at W116 showed no hits for 1 , and biocatalytic characterisation of all 20 variants showed that W116I is not the best engineered residue for this position . Nevertheless, our NCR data support the importance of hotspot position III itself.…”
Section: Resultsmentioning
confidence: 60%
“…Nevertheless, our NCR data support the importance of hotspot position III itself. Taking all evidence together, it appears that residues at hotspot position III are fine‐tuning reactivity, either alone or together with other hotspot positions …”
Section: Resultsmentioning
confidence: 98%
“…Substitution against more bulky residues resulted in a switch of stereoselectivity affording the (R)-enantiomer. This tryptophan is conserved for classes I and II enzymes and might be a major residue for changing enantioselectivity of different prochiral substrates [25]. Class III enzymes possess a conserved alanine at this position.…”
Section: Classification Of Oyes With Respect To Substratesmentioning
confidence: 99%
“…Catalysts 2017, 7, 130 2 of 24 activated alkenes with an electron withdrawing group (EWG) such as aldehyde, ketone, anhydride [8,10,11], nitro [9,12,13], (di)ester [8,[14][15][16][17], (di)carboxylic acid [18][19][20], cyclic imide [21][22][23], nitrile [24], β-cyanoacrylate [25], β-nitroacrylate [26], and several other functional groups [27]. There are many examples of the high industrial potential of OYEs for the synthesis of valuable target products [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity of experimental data on the bioreduction of -nitroketones, especially for aromatic derivatives, and the current need for biocatalysed synthesis of chiral building blocks for pharmaceutical applications [27][28][29][30][31] led us to investigate the use of commercial alcohol dehydrogenases for the enantioselective reduction of aryl and alkyl α-nitroketones 3 in controlled reaction conditions. We also studied the further manipulation of specific nitroalcohols 1 to prepare aminoalcohols 2, which have been already employed as key intermediates for the synthesis of active pharmaceutical ingredients, such as levamisole and (R)-tembamide.…”
Section: Synthesis Of Nitroketones 3 and Biocatalysed Reduction To Dementioning
confidence: 99%